Seeking new prognostic and predictive factors in patients with metastatic renal cell carcinoma – apoptosis-regulating factors - Młot, Beata; Szczylik, Cezary; Rzepecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2012)
Kidney cancer, despite the constant upward trend in the incidence of this type of cancer (about 1.5-5.9% per year), is rather rare, representing approximately 2-3% of all adult cancers. Since recently, drugs based on so-called targeted therapy play a decisive role in the treatment of patients with metastatic kidney cancer. Prognostic and predictive factors can significantly contribute to prognosis assessment and the correct classification of patients to specific forms of causal treatment of kidney cancer. In addition to the most commonly used and widely known prognostic factors, grouped in the so-called Motzer model, new prognostic markers of this tumour are being sought. Preliminary reports indicate that there may be a promising role of factors that regulate the cell cycle and apoptosis, and agents from the group of hypoxia-induced proteins. The proliferation markers or proteins related to cellular adhesion can also be relevant. This article presents examples of markers from the first of the above groups of proteins, which on the basis of the performed analyses showed independent prognostic or predictive value in kidney cancer.